2017
DOI: 10.1109/tmc.2016.2538230
|View full text |Cite
|
Sign up to set email alerts
|

Toward a Wearable RFID System for Real-Time Activity Recognition Using Radio Patterns

Abstract: Elderly care is one of the many applications supported by real-time activity recognition systems. Traditional approaches use cameras, body sensor networks, or radio patterns from various sources for activity recognition. However, these approaches are limited due to ease-of-use, coverage, or privacy preserving issues. In this paper, we present a novel wearable Radio Frequency Identification (RFID) system aims at providing an easy-to-use solution with high detection coverage. Our system uses passive tags which a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…One major drawback of a single accelerometer is that they easily fail to discriminate similar activities. Besides an accelerometer, RFID technology is widely used, and it also helps to recognize human activities [25]. For example, Kim et al [26] constructed an indoor healthcare monitoring system to track the elderly who wore RFID tags.…”
Section: Related Workmentioning
confidence: 99%
“…One major drawback of a single accelerometer is that they easily fail to discriminate similar activities. Besides an accelerometer, RFID technology is widely used, and it also helps to recognize human activities [25]. For example, Kim et al [26] constructed an indoor healthcare monitoring system to track the elderly who wore RFID tags.…”
Section: Related Workmentioning
confidence: 99%
“…The simulation results of the work of the aforementioned authors showed smaller positioning error compared to that of other methods. The later study proposed using RFID to detect activities in elderly people; it suggests attaching RFID tags onto clothing of the elderly people, having them carry RFID readers, installing UHF RFID readers indoors, and collecting different positions of the elderly people and the received signal strength of RFID during different activities; the collected data is then run through support vector machines for learning and categorizing signals and behaviors, so that when a mobile phone registers RFID received signal strength, it can determine current position and behavior of the elderly people. Since the aforementioned approach focuses on positioning the indoor location of elderly people and requires equipment such as mobile devices and RFIDs, which can be troublesome for elderly people in terms of portability and operation, such as battery maintenance, the positioning feature of this research emphasizes beacon power, received signal strength, and state machines so as to reduce the number of sensor installations needed and hardware costs.…”
Section: Related Workmentioning
confidence: 99%
“…Table is an analysis of differences between our proposed method and studies . The analysis features comparison of factors including complexity of system operation, number of sensors required, frequency of battery change, cost for system establishment, and adaptability of system environment.…”
Section: Performance Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The measured performance indicates a possible application of these body-worn tags for continuous tracking of human movements. A study on wearable RFID based system for real-time activity recognition is conducted in [75], where recognition is realised by exploiting RFID radio patterns towards easy-to-use solution and high detection coverage. In addition to custom-designed systems, there are specific RFID based platforms suitable for human activity detection, such as iGlove, iBracelet, and WISP [76].…”
Section: F Human Activity Recognitionmentioning
confidence: 99%